Injuries and illnesses in Swedish para athletes during the Paralympic Games 2012-2018 - Dahlén, S. (GIH - The Swedish School of Sport and Health Sciences, 2021)
The aim of the study was to analyse the injuries and illnesses in Swedish Para athletes during four Paralympic Games (PG), 2012-2018. The research questions (RQ) were: 1) what was the injury incident rate (IR), and which anatomical areas were affected by injuries? 2) what was the illness IR and which physiological systems were affected by illnesses? 3) did the injury and illness IR differ between the Swedish delegation and the reference group (RG), where most athletes participating in the four PGs were included? 4) were there any associations between injury and illness IR and subgroups of athletes? Method: A retrospective analysis of data from a large ongoing prospective study of injuries and illnesses initiated by the International Paralympic Committee in 2012. Data from 157 Swedish Paralympic athletes were analysed and compared to previous results from the RG. For RQ1, 2 and 3, injuries and illnesses were reported as IR, calculated per 1000 athlete days, in the Swedish delegations (RQ1-3) and compared to the RG (RQ3). For RQ4, a univariate logistic regression analysis was conducted to find possible associations between risk of injury and illness, and subgroups. Results: The injury IR in Swedish athletes varied between the four PGs, from 2.5 to 59.5 per 1000 athlete days. Most injuries occurred in the upper limb. There was a particularly high occurrence of injuries in Para ice hockey players. The illness IR varied from 3.6 per 1000 athlete days in London (2012), to 39.5 in Sochi (2014). The respiratory tract was most affected by illness, in both Swedish athletes and the RG. Most injuries and illnesses in the Swedish delegation were acute onset, but only a minority led to days lost from training and competition. The Swedish delegation had a lower injury IR per 1000 athlete days compared to the RG in all PGs, except for Pyeongchang (2018), where they had an almost three times higher IR. The illness IR for the Swedish delegation was, compared to the RG, lower in London (2012), the same in Rio (2016) and higher in both Sochi (2014) and Pyeongchang (2018). Participation in the Winter Games was associated with a higher risk for both injury and illness compared to the Summer Games. There was also an increased risk of injury for athletes in a contact sport compared to a non-contact sport. Conclusions: This thesis indicates that there is a need to continue monitoring Para athletes, both during and between competitions, to get more knowledge about injury and illness incidence patterns, as well as preventable risk factors. The latter would be especially important for Para ice hockey. It is yet to see if the awareness of the importance of hygiene measures and physical distancing to reduce spreading of infections, brought on by the Covid-19 pandemic, will affect the occurrence of respiratory tract infections during large sporting events.